I am feeling so good! Motivations for interacting in online brand communities - Bilro, R. G.; Loureiro, S. M. C. (Journal of Research in Interactive Marketing, 2023)
Purpose – This paper focuses on customer engagement in online brand communities (OBCs). Drawing upon self-determination theory (SDT), the research proposes a conceptual model portraying the effect of intrinsic and extrinsic motivations on hedonic and utilitarian rewards, which the authors posit will affect subjective wellbeing (SWB) and brand advocacy. Design/methodology/approach – Data collected through a questionnaire completed by 367 members of OBC were employed to test the structural theory using partial least squares-structural equation modelling (PLS-SEM). Findings – The empirical results reveal that intrinsic motivations significantly and positively affect hedonic and utilitarian rewards, but the same does not apply to extrinsic motivations. The results also confirm that hedonic and utilitarian rewards are significantly related to brand advocacy and SWB, although with different strengths. Originality/value – This study provides new insights to the emerging research on customer engagement in OBC, including its motivations and rewards for contributing to these communities, from an SDT perspective. In addition, this paper offers a novel approach, by introducing brand advocacy and SWB as consequences of customer engagement in OBCs.